Pelecehan Seksual Terhadap Model Perempuan dalam Prespektif Hukum Islam (Studi Kasus di Banjarnegara) - Putra, Nandaswara Shandi (UM Purwokerto Press, 2024)
This research aims to understand the phenomenon of sexual harassment against female models in Banjarnegara from the perspective of Islamic law and the Criminal Code. This research uses a qualitative research method with a case study research type. Research data was obtained through interviews with victims of sexual harassment, perpetrators of sexual harassment, victims' families, law enforcement officers, and community leaders in Banjarnegara. The research results show that sexual harassment against female models in Banjarnegara is a serious problem. Modes of sexual harassment that often occur include physical and verbal harassment. The factors behind the occurrence of sexual harassment are the perception that women are weak and powerless, patriarchal culture, and lack of law enforcement. Sanctions for sexual harassment according to Islamic law and the Criminal Code vary. In Islamic law, sexual harassment is included in the category of zina and is punishable by had. Meanwhile, in the Criminal Code, sexual harassment is regulated in Articles 281, 282, 283 and 285, with the threat of a maximum criminal penalty of two years and eight months or a maximum fine of IDR 4,500. This research recommends several steps to prevent sexual harassment against female models in Banjarnegara, including: Increasing education about gender equality and women's rights, Strengthening law enforcement against perpetrators of sexual harassment, Providing assistance and protection for victims of sexual harassment.